Behavioral Change Communication and Vaccine Acceptance: A Framework for Strengthening Public Trust in Health Interventions - Yenny Budiman Makahaghi (Journal of Nutrition and Health Care, 2025)
Vaccine hesitancy remains a global challenge that threatens public health achievements, particularly in the post-pandemic era. Beyond scientific efficacy, vaccine acceptance is largely determined by how health messages are communicated, perceived, and trusted. Behavioral Change Communication (BCC) provides a framework that integrates psychological, social, and cultural factors to encourage informed and voluntary participation in vaccination programs. This study aims to examine the conceptual role of BCC in promoting vaccine acceptance and rebuilding public trust in health interventions, focusing on its application within the Indonesian context. A qualitative conceptual analysis was conducted using literature published between 2019 and 2025. The study synthesized theoretical models such as the Health Belief Model (HBM) and the Social Ecological Model (SEM), along with national and international reports on vaccine communication and public behavior. The findings highlight that empathetic, transparent, and participatory communication strategies are key to overcoming misinformation and strengthening public trust. BCC operates through four dimensions message design, media selection, community participation, and behavioral reinforcement each contributing to sustained vaccine confidence. Digital communication platforms further expand outreach but require ethical regulation to prevent misinformation. BCC should be institutionalized as a core strategy in vaccination programs and public health policy. By fostering dialogue, empathy, and community engagement, health systems can transform communication from one-way persuasion into genuine partnership, leading to improved vaccine acceptance and collective health resilience.